2015
DOI: 10.3109/00016489.2015.1021932
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between benign paroxysmal positional vertigo and thyroid autoimmunity

Abstract: In the study, eight patients of the BPPV group (16%) had a high thyroid antibody level. In the non-BPPV group, six patients (11.5%) had elevated thyroid antibodies. In the control group, 15 patients (25%) had elevated thyroid antibodies. TSH values of all subjects were detected to be within normal range. No statistical difference was found between the groups with respect to TG-Ab and TPO-Ab values (p-values = 0.729 and 0.812, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
3
18
1
2
Order By: Relevance
“…However, another study showed no significant difference in the level of thyroid-stimulating hormone, anti-thyroid peroxidase antibody, or anti-thyroglobulin antibody between patients with and without BPPV. 89…”
Section: Autoimmune Inflammatory or Rheumatologic Disordersmentioning
confidence: 99%
“…However, another study showed no significant difference in the level of thyroid-stimulating hormone, anti-thyroid peroxidase antibody, or anti-thyroglobulin antibody between patients with and without BPPV. 89…”
Section: Autoimmune Inflammatory or Rheumatologic Disordersmentioning
confidence: 99%
“…Sari et al studied the relationship between HT and BPPV; their study was one of the few that analysed the relationships between levels of thyroid-stimulating hormone (TSH), anti-TPO, and anti-TG antibodies and the co-occurrence of BPPV. In a group of 52 patients with BPPV, the authors did not find any statistical relationship between the occurrence of symptoms, their severity, and the presence of anti-TPO antibodies or elevated TSH level despite the fact that 16% of patients had high thyroid antibody levels [28].…”
Section: Hashimoto's Thyroiditismentioning
confidence: 83%
“…Otoliths may be detached due to head trauma, viral infection, following middle ear surgery, or as a result of ototoxic drugs. Autoimmunity is suspected to be involved in this phenomenon [28,29]. Modungo et al found elevated anti-TPO and anti-TG antibodies in patients with po-REVIEW peutic doses reduced the level of anti-TG antibodies in patients with HT [33][34].…”
Section: Benign Paroxysmal Positional Vertigomentioning
confidence: 99%
See 2 more Smart Citations